Why Islamic banks are reluctant to offer musharakah mutanaqisah for home financing: the case of Maybank Islamic and Affin Islamic Bank - M A Zaaba, Nurul Iffah; Hassan, Rusni (Research Center Islamic Economics-IKAM, 2019)
his paper focuses on the challenges faced by the Malaysian Islamic Banks in implementing Musharakah Mutanaqisah (MM) Home Financing. Even though the study is specifically on the Malaysian Islamic banks, but the issues and recommendations addressed in this study are also pertinent to other Islamic banks across the world since they are also offering it. Drawing upon in-depth semi-structured interviews with the senior officers in two leading Islamic banks in Malaysia, one is the bank which terminated its MM Home Financing products however the other one continues to offer it. Knowing the contradicting perspectives of both banks gives insight of the real challenges faced by them in offering MM for home financing which are advance rental and the system’s incapability to capture the unique nature of MM, and at the same time to know the motivation of offering it i.e. product diversification and comprehensive risk mitigation. This paper concludes by making recommendations that may be adopted by Islamic banks and the regulators to facilitate the promotion of MM Home Financing. Notably, this paper offers empirical findings which are different from the previous literature.